2016
DOI: 10.2807/1560-7917.es.2016.21.9.30149
|View full text |Cite
|
Sign up to set email alerts
|

Presence of mcr-1-positive Enterobacteriaceae in retail chicken meat but not in humans in the Netherlands since 2009

Abstract: Recently, the plasmid-mediated colistin resistance gene mcr-1 was found in Enterobacteriaceae from humans, pigs and retail meat in China. Several reports have documented global presence of the gene in Enterobacteriaceae from humans, food animals and food since. We screened several well-characterised strain collections of Enterobacteriaceae, obtained from retail chicken meat and hospitalised patients in the Netherlands between 2009 and 2015, for presence of colistin resistance and the mcr-1 gene. A total of 2,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 26 publications
3
61
0
1
Order By: Relevance
“…reported a plasmid-borne colistin resistant gene ( mcr-1 ) from China14, which was quickly reaffirmed in strains isolated from Denmark15, Germany16, France17, Netherland18, Switzerland19, United States20, Belgium21, Italy22 and Vietnam23. This indicates global spreading of bacteria harboring this plasmid-borne colistin resistance.…”
mentioning
confidence: 89%
“…reported a plasmid-borne colistin resistant gene ( mcr-1 ) from China14, which was quickly reaffirmed in strains isolated from Denmark15, Germany16, France17, Netherland18, Switzerland19, United States20, Belgium21, Italy22 and Vietnam23. This indicates global spreading of bacteria harboring this plasmid-borne colistin resistance.…”
mentioning
confidence: 89%
“…The fact that plasmid-mediated colistin resistance originated from animals combined with the much larger use of colistin in animals than in humans, has contributed to the perception that the problem needs to be tackled first in veterinary medicine. As documented by Kluytmans-van den Bergh et al, mcr-1-positive isolates have so far only been found sporadically in humans in Europe [2]. This could be due to absence of selection in a non-favourable environment as indicated by the fact that all travellers that were tested positive for mcr-1 upon return were negative after one month [3].…”
mentioning
confidence: 94%
“…In this issue, Kluytmans-van den Bergh et al report on their finding of the mcr-1 gene in Escherichia coli isolates from three (1.5%) of 196 samples of chicken meat collected at Dutch supermarkets, one in 2009 and two in 2014 [2]. This was done by whole genome sequencing of all E. coli isolates and then screening for the presence of the mcr-1 gene by comparing the assembled sequences with sequence data from two databases.…”
mentioning
confidence: 99%
“…These strains (especially Escherichia coli) have been isolated worldwide from humans (1,(3)(4)(5)(6)(7)(8)(9)(10), food-producing animals (4,6,(11)(12)(13)(14), the food chain (7,10,(15)(16)(17), and the environment (4,15). However, most of these studies searched for mcr-1 in previously stored extended-spectrum cephalosporinresistant Enterobacteriaceae (ESC-R-Ent) (8,12,13,15,17). This leads to a question about the actual prevalence of mcr-1-positive Enterobacteriaceae (mcr-1-Ent), especially because mcr-1 can be carried by plasmids not coharboring extended-spectrum ␤-lactamase (ESBL), plasmid-mediated AmpC (pAmpCs), and/or carbapenemase genes (5,7,12,14,18).…”
mentioning
confidence: 99%